Local Community Participation in Protection Area of Water Resources Conservation in the Rinjani Forest Management Unit (Fmu) of Rinjani Barat, Lombok Island - Sukardi, Sukardi; Dipokusumo, Bambang; Idris, Muhamad Husni (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
The objectives of this study are: (1) to examine the participation of local communities in the conservation of water resources, (2) to analyze the determinants of participation, and (3) to formulate a participatory water resource conservation model. This research was carried out in the area of ​​West Rinjani Protection Forest Management Unit (KPHL). Data and information were collected by means of interview, in-depth interview, document tracking, and observation. Data were analysed descriptively. Multiple regression with logistic models was used to analyze the determinant of participation. Results showed that (1) local community participation in the conservation of water resources in the Rinjani Barat KPHL area is high (more than 40%); (2) community involvement are in the form of protection of springs, preservation of catchment areas, maintenance of canals, and utilization/management of natural tourism; (3) determinants of local community participation in the conservation of water resources are age, distance of the house from the forest area, and length of stay in the area; (4) a participatory and sustainable spring conservation model is the economic empowerment of the local community through the development of Non Timber Forest Product (NTFP) small businesses and the development of ecotourism.